Konstruksi Sosial pada Pedagang Tradisional dalam Menghadapi Era Kompetisi Perdagangan Bebas - Komara, Beni Dwi; Prasetya, Agus (Jurnal Riset Entrepreneurship, 2019)
Article 33 of the 1945 Constitution aspires to the Indonesian economy being managed by the state with the aim of the prosperity of the Indonesian people. But the fact is that prosperity is only enjoyed by certain people and certain groups because the economy is only controlled by those who are only a small part of the Indonesian people. The growth of super markets, modern retail stores such as IndoMart, AlfaMart in all corners of the country, both villages and cities, has displaced traditional markets and caused traditional traders to go out of business. This is a violation of the constitution and must be stopped. Traditional traders are populist economic actors in the economic system, so the state must not commit arbitrariness, such as allowing competition, unhealthy competition between traditional traders and modern retail traders. This study aims: a). Knowing the need for social construction to traditional traders, b). what is the impact of the presence of modern retailers on traditional markets, c). the response of traditional traders to the mushrooming of IndoMart and AlfaMart, d). How should the local government protect Traditional market traders. This study uses a qualitative approach, with its social paradigm of social definition. Data retrieval through in-depth interviews, observation, documentation, while data analysis uses Interactive Miles and Hubermann Models. The results of the study show that it was necessary to do "Social Reconstruction" to traditional traders. The presence of modern markets has resulted in declining sales levels, the flight of buyers from the â€œSlekoâ€ market, â€œBesarâ€ market, and other traditional markets. This condition creates an "economic shock" for traditional traders because they felt their territory is "robbed" by traders who have large capital. If this condition is left uncontrolled, it would create social insecurity, namely traders become unemployed, beggars, which shall trigger an increase in crime rates. Local governments must act quickly by doing "Social Trader Reconstruction Traditional". A policy that was oriented to the economy of the people to revive traditional markets and allow traditional traders to resell. Don't treat people only become social objects! Economy, politics of politicians and regional governments at certain times such as the regional elections and the presidential election